Body appreciation around the world: Measurement invariance of the Body Appreciation Scale-2 (BAS-2) across 65 nations, 40 languages, gender identities, and age - Swami, Viren; Tran, Ulrich S.; Stieger, Stefan; Aavik, Toivo; Ranjbar, Hamed Abdollahpour; Adebayo, Sulaiman Olanrewaju; Afhami, Reza; Ahmed, Oli; Aimé, Annie; Akel, Marwan; Halbusi, Hussam Al; Alexias, George; et al. (Elsevier, 2023)
The Body Appreciation Scale-2 (BAS-2) is a widely used measure of a core facet of the positive body image construct. However, extant research concerning measurement invariance of the BAS-2 across a large number of nations remains limited. Here, we utilised the Body Image in Nature (BINS) dataset – with data collected between 2020 and 2022 – to assess measurement invariance of the BAS-2 across 65 nations, 40 languages, gender identities, and age groups. Multi-group confirmatory factor analysis indicated that full scalar invariance was upheld across all nations, languages, gender identities, and age groups, suggesting that the unidimensional BAS-2 model has widespread applicability. There were large differences across nations and languages in latent body appreciation, while differences across gender identities and age groups were negligible-to-small. Additionally, greater body appreciation was significantly associated with higher life satisfaction, being single (versus being married or in a committed relationship), and greater rurality (versus urbanicity). Across a subset of nations where nation-level data were available, greater body appreciation was also significantly associated with greater cultural distance from the United States and greater relative income inequality. These findings suggest that the BAS-2 likely captures a near-universal conceptualisation of the body appreciation construct, which should facilitate further cross-cultural research.
Keywords: Body appreciation; Body appreciation Scale-2 (BAS-2); Cross-cultural; Measurement invariance; Multi-group confirmatory factor analysis (MG-CFA); Psychometrics; Structural analysis